Unifying terminology, reporting, and bowel preparation standards in colon capsule endoscopy: Nyborg Consensus - Lei, Ian Io; Koulaouzidis, Anastasios; Schelde-Olesen, Benedicte; Turvill, James; Cortegoso Valdivia, Pablo; Rondonotti, Emanuele; Plevris, John N.; Keuchel, Martin; Saurin, Jean-Christophe; Dray, Xavier; Brodersen, Jacob Broder; McAlindon, Mark; Toth, Ervin; Robertson, Alexander; Arasaradnam, Ramesh (Endoscopy International Open, 2025)
Colon capsule endoscopy (CCE) is becoming increasingly popular in Europe. However, development of quality assurance and standardized terminology has not kept pace with clinical integration of this technology. As a result, there are significant variations in reporting standards, highlighting the need for a standardized terminology and framework. We used the RAND process to achieve a consensus of experts to determine the terminology in CCE, bowel cleansing assessment, and quality assurance reporting and future research priorities.A panel comprising 14 European CCE experts evaluated 45 statements during the international REFLECT symposium (Nyborg, Denmark) through three survey rounds and face-to-face and virtual discussions in the initial two rounds. Participants anonymously rated statement appropriateness.Twenty-eight consensus statements were developed. Eight statements focus on consistent terminology for confirming CCE-detected polypoid and inflammatory colonic lesions with colonoscopy. To ensure standardization and quality assurance, 13 mandatory fields were recommended for inclusion in a CCE report. Three endorsed reporting methodologies were suggested, emphasizing prompt notification for suspected malignant findings, recommending a generic disclaimer regarding stomach and small bowel visualization intentions, and establishing reporting timelines at an interdepartmental level based on urgency. Four bowel preparation scale-related statements led to the recommendation to adoptithe Colon Capsule CLEansing Assessment and Reporting (CC-CLEAR) scale as the preferred scale.This study established a framework for terminology, reporting, and assessment of bowel cleansing for CCE. Future research should focus on optimizing bowel preparation regimens and exploring artificial intelligence applications in CCE.
Keywords: Endoscopy Lower GI Tract; Polyps / adenomas / ...; Colorectal cancer; CRC screening; Diagnosis and imaging (inc chromoendoscopy, NBI, iSCAN, FICE, CLE...); Endoscopy Small Bowel; Capsule endoscopy